POLA ASUH ORANGTUA DEMOKRATIS, EFIKASI-DIRI DAN KREATIVITAS REMAJA - Djalali, M. As’ad (Persona:Jurnal Psikologi Indonesia, 2012)
Abstract, Research for studies both simultaneous or partial correlation of democratic parenting and self-efficacy to creativity. Subject are 123 mid adolescence (60 boys  and 63 girls), ages from 16 to 18 years old. Data taken from scales of C.O.R.E for creativity, P.A.O.D for democatic parenting and ED-G for self-efficacy. Result of simultaneous test is R =  0,384, F =  10,349, p = 0,000 (p < 0,05). Democratic parenting and self-efficacy simultaneously and significant would have predicting creativity. R2 =  0,147 refer that 14,7% varians proportion on creativity would have explained from democratic parenting and self-effiacy, other for 85,3% could explained from other factors that not analyzed. Constant of 146,671 is score of creativity if no democratic parenting and self-efficacy. Result of partial test of democratic parenting t = 0,420, p = 0,675 (p > 0,05). Democratic parenting partially wasn’t correlated with creativity. Result of partial test of self-efficacy t = 4,534, p = 0,000 (p < 0,05). Self-efficacy partially was significantly positive correlated with creativity. The findings are discussed in terms of their implications for mid adolescent context. Key words: creativity, democratic parenting, self-efficacy